Kurikulum Pendidikan Jasmani Olahraga di Perguruan Tinggi dan Implementasinya - R. Agung Purwandono Saleh (Departement of Mathematics Education, 2024)
The purpose of this study was to determine the Physical Education and Sports Curriculum in Higher Education and its Implementation. This research was conducted at UPN